Pengaruh Return on Assets, Debt to Equity Ratio dan Current Ratio Terhadap Harga Saham Perusahaan Sub Sektor Transportasi Selama Pandemi Covid-19 - Sohilauw, Muhammad Atarafly Simasima; eiwakabessy, Theophilia Fina F L; Sososutiksno, Christina (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2022)
This study was aimed to exemined the effect of of return on assets, debt to equity ratio and current ratio on stock prices. The population in this study are all transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX). The sample used in this study were 45 companies selected using purposive sampling technique. Analysis using multiple regression analysis. The results showed that return on assets not significantly affect the stock prices. While the Debt to Equity Ratio and Current Ratio have a negative effect on stock prices